The General Ordinances of the City of Indianapolis. Containing also, Acts of the Indiana General Assembly so far as they Control Said City, to which Prefixed a Chronological Roster of Officers fro, 1832 to 1895 and Rules Governing the Common Council. Revision of 1895 Page 230, § 12-15 - (:unkn) unknown (General Publisher, 1895)
The Chief Fire Engineer shall search any building in the compact portion of the city where there shall be cause to suspect the keeping of gunpowder in quantities over twenty-five pounds. Violators shall have powder seized, fined not less than five nor more than fifty dollars. Owners of said buildings shall be fined not less than one nor more than ten dollars for every day such gunpowder shall be stored or kept.
--
Keywords: GUN POWDER STORAGE